Analytic rubric scoring versus comparative judgment: a comparison of two approaches to assessing spoken-language interpreting - Han, Chao (Meta, 2021)
In this article, we report on an empirical study conducted to evaluate the utility of analytic rubric scoring (ARS) vis-à-vis comparative judgment (CJ) as two approaches to assessing spoken-language interpreting. The primary motivation behind the study is that the potential advantages of CJ may make it a promising alternative to ARS. When conducting CJ on interpreting, judges need to compare two renditions and decide which one is of higher quality. Such binary decisions are then modeled statistically to produce a scaled rank order of the renditions from “worst” to “best.” We set up an experiment in which two groups of raters/judges of varying scoring expertise applied both CJ and ARS to assess 40 samples of English-Chinese consecutive interpreting. Our analysis of quantitative data suggests that overall ARS outperformed CJ in terms of validity, reliability, practicality and acceptability. Qualitative questionnaire data helped us obtain insights into the judges’/raters’ perceived advantages and disadvantages of CJ and ARS. Based on the findings, we tried to account for CJ’s underperformance vis-à-vis ARS, focusing on the specificities of interpreting assessment. We also propose potential avenues for future research to improve our understanding of interpreting assessment.